18
$\begingroup$

How to show that? $$\sum_{n=1}^{\infty}\left(\frac{\sin(22n)}{7n}\right)^3=\frac{1}{2}\left(\pi-\frac{22}{7}\right)^3$$

I have no ideas to prove it, but it seems correct via Wolfram's calculator

$\endgroup$
  • 2
    $\begingroup$ Looks related to this one, also here. See if it helps you to start ... $\endgroup$ – rtybase May 27 at 21:18
  • $\begingroup$ This also seems to hold if you replace the pair $(22,7)$ with $(3,1)$ or $(355,113)$... $\endgroup$ – Carl Schildkraut May 27 at 22:50
  • $\begingroup$ @CarlSchildkraut Could be something to do with the $\pi$ continued fraction? $\endgroup$ – Anvit May 28 at 5:08
  • $\begingroup$ @Anvit That was my guess; it also seems to work for $(4,1)$ as well though. $\endgroup$ – Carl Schildkraut May 28 at 6:44
  • 1
    $\begingroup$ As well, something to do with Fourier series ? $\endgroup$ – Jean Marie May 28 at 8:03
18
$\begingroup$

First some preliminary work that will be used later:

We have for $x\in(0,2\pi)$ $$\frac{\pi-x}{2}=\sum_{n=1}^\infty\frac{\sin(nx)}{n}$$ Shifting by $6\pi$ we have for $x\in (6\pi, 8\pi)$ $$\frac{7\pi-x}{2}=\sum_{n=1}\frac{\sin(nx)}{n} \tag1 $$ Or similarly for $x\in (20\pi,22\pi)$ $$\frac{21\pi-x}{2}=\sum_{n=1}\frac{\sin(nx)}{n}\tag 2$$

Integrating $(1)$ with respect to $x$ yields $$\sum_{n=1}\frac{\cos(nx)}{n^2}=\frac{(7\pi-x)^2}{4}+C$$ Now set $x=7\pi$ to get $C=-\frac{\pi^2}{12}$ and integrate again $$\sum_{n=1}^\infty \frac{\sin(nx)}{n^3}=-\frac{(7\pi-x)^3}{12}-\frac{\pi^2}{12}x+K$$ And finally put $x=7\pi $ to get $K=7\pi\cdot \frac{\pi^2}{12}$. Thus for $x\in(6\pi,8\pi)$ we have $$\sum_{n=1}^\infty \frac{\sin(nx)}{n^3}=-\frac{(7\pi-x)^3}{12}-\frac{\pi^2}{12}x+\frac{7\pi^3}{12}\tag3$$ Similarly things for $(2)$ yields for $x\in(20\pi,22\pi)$ $$\sum_{n=1}^\infty \frac{\sin(nx)}{n^3}=-\frac{(21\pi-x)^3}{12}-\frac{\pi^2}{12}x+\frac{21\pi^3}{12}\tag4$$


Now back to the original sum. We have the formula $4\sin^3 x =3 \sin x-\sin(3x) $ so $$S=\sum_{n=1}^{\infty}\left(\frac{\sin(22n)}{7n}\right)^3=\frac{1}{4\cdot 7^3}\left(3\sum_{n=1}^\infty \frac{\sin(22n)}{n^3}-\sum_{n=1}^\infty \frac{\sin(66n)}{n^3}\right)=\frac{1}{4\cdot 7^3}\left(3S_1-S_2\right)$$ Now things are easy because for $S_1$ we can set $x=22$ in $(3)$ and for $S_2$ we can set $x=66$ in $(4)$. $$ S_1=\sum_{n=1}^\infty \frac{\sin(22n)}{n^3}=-\frac{(7\pi-22)^3}{12}-\frac{22\pi^2}{12}+\frac{7\pi^3}{12}$$ $$S_2=\sum_{n=1}^\infty \frac{\sin(66n)}{n^3}=-\frac{(21\pi-66)^3}{12}-\frac{66\pi^2}{12}+\frac{21\pi^3}{12}$$ $$\Rightarrow S=\frac{1}{4\cdot 7^3}\left((7\pi-22)^3\left(-\frac3{12} +\frac{3^3}{12}\right)\right)=\frac{1}{2}\left(\pi-\frac{22} {7}\right)^3$$


Generalization. We have for $x\in\left((k-1)\pi,(k+1)\pi\right)$ $$\frac{k\pi-x}{2}=\sum_{n=1}^\infty \frac{\sin (nx)}{n}$$ $$\Rightarrow \sum_{n=1}^\infty \frac{\sin(nx)}{n^3}=-\frac{(k\pi-x)^3}{12}-\frac{\pi^2}{12}x+\frac{k\pi^3}{12}$$ And for $x\in\left((3k-1)\pi,(3k+1)\pi\right)$ $$\sum_{n=1}^\infty \frac{\sin(nx)}{n^3}=-\frac{(3k\pi-x)^3}{12}-\frac{\pi^2}{12}x+\frac{3k\pi^3}{12}$$ Here is where the magic happens: $$S(a,b)=\sum_{n=1}^\infty \frac{\sin^3(an)}{(bn)^3}=\frac{1}{4b^3}\left(3\sum_{n=1}^\infty \frac{\sin(an)}{n^3}-\sum_{n=1}^\infty \frac{\sin(3an)}{n^3}\right)$$ $$=\frac{1}{4b^3}\left(-3\frac{(k\pi-a)^3}{12}-\frac{3\pi^2}{12}a+\frac{3k\pi^3}{12}+\frac{(3k\pi-3a)^3}{12}+\frac{3\pi^2}{12}a-\frac{3k\pi^3}{12}\right)$$ $$=\frac{1}{4b^3}\left((k\pi-a)^3 \left(-\frac{3}{12}+\frac{27}{12}\right)\right)=\frac{1}{2b^3}(k\pi-a)^3$$ So for example a random series: $$S(123,321)=\sum_{n=1}^\infty \frac{\sin^3(123n)}{(321n)^3}=\frac{1}{2\cdot(321)^3}(39\pi-123)^3$$ If we set $b=k$ we get quite interesting things, mostly those combinations are found here, but the series is evaluable in an elementary form for any pair of numbers.

$\endgroup$
  • 2
    $\begingroup$ Probably you should mention that the "magic" (perfect cube) happens only for one third of integer numbers (see my comment to the answer of Claude Leibovici). Both $a=22$ and $a=123$ are such numbers (as well as other integer numbers close to an odd multiple of $\pi$). $\endgroup$ – user May 29 at 9:54
  • 1
    $\begingroup$ I was also thinking the generalization works only if both $a \in ((k-1)\pi, (k+1)\pi)$ and $3a \in ((3k - 1)\pi, (3k + 1)\pi)$, which means in fact $a \in ((k - 1/3)\pi, (k+1/3)\pi)$. This is a stronger condition, and is not satisfied for example by $a = 2$. But at least it does ensure uniqueness of the $k$, if it exists. $\endgroup$ – Tob Ernack May 29 at 16:05
  • 1
    $\begingroup$ For the cases not covered above, you can probably choose a different $k$ for the sum of $\frac{\sin(3an)}{n^3}$ than for the sum of $\frac{\sin(an)}{n^3}$ and a similar result should work. $\endgroup$ – Tob Ernack May 29 at 16:12
  • 1
    $\begingroup$ Damn, you're like Euler reincarnate. $\endgroup$ – clathratus Jun 27 at 21:47
  • $\begingroup$ Haha, not even close. That guy could do anything, here is just a fluke.// Euler was doing Feynman's tricks before Feynman was even born :D $\endgroup$ – Zacky Jun 28 at 6:55
8
$\begingroup$

Too long for a comment.

I think that we could make amazing identities for the more general case of $$S_{a,b}=\sum_{n=1}^{\infty}\left(\frac{\sin(an)}{bn}\right)^3=\frac 1{b^3}\sum_{n=1}^{\infty}\left(\frac{\sin(an)}{n}\right)^3$$ Using first $$\sin ^3(a n)=\frac{3}{4} \sin (a n)-\frac{1}{4} \sin (3 a n)$$ $$S_{a,b}=\frac{3}{4b^3}\sum_{n=1}^{\infty}\frac{\sin(an)}{n^3}-\frac{1}{4b^3}\sum_{n=1}^{\infty}\frac{\sin(3an)}{n^3}$$ which is the imaginary part of $$T_{a,b}=\frac{3}{4b^3}\sum_{n=1}^{\infty}\frac{e^{ian}}{n^3}-\frac{1}{4b^3}\sum_{n=1}^{\infty}\frac{e^{3ian}}{n^3}$$ and now use the fact that $$\sum_{n=1}^{\infty}\frac{e^{ikn}}{n^3}=\text{Li}_3\left(e^{i k}\right)$$ As a result $$S_{a,b}=\frac{i}{8 b^3} \left(3 \text{Li}_3\left(e^{-i a}\right)-3 \text{Li}_3\left(e^{i a}\right)-\text{Li}_3\left(e^{-3 i a}\right)+\text{Li}_3\left(e^{3 i a}\right)\right)$$

Now, for the present case, $$i \left(\text{Li}_3\left(e^{-22 i}\right)-\text{Li}_3\left(e^{22 i}\right)\right)=-\frac{2}{3} (3 \pi -11) (4 \pi -11) (7 \pi -22)$$ $$i \left(\text{Li}_3\left(e^{-66 i}\right)-\text{Li}_3\left(e^{66 i}\right)\right)=-22 (\pi -3) (7 \pi -22) (10 \pi -33)$$ make $$S_{22,b}=\frac{(7 \pi -22)^3}{2 b^3}=\frac 12\left(\frac{7\pi}b-\frac {22} b \right)^3$$

In fact, exploring the cases where $$i\left(3 \text{Li}_3\left(e^{-i a}\right)-3 \text{Li}_3\left(e^{i a}\right)-\text{Li}_3\left(e^{-3 i a}\right)+\text{Li}_3\left(e^{3 i a}\right)\right)$$ is a multiple of a perfect cube, up to $a=100$ is found the sequence $$\{3,4,9,10,15,16,21,\color{red}{22},23,28,29,34,35,40,41,47,48,53,54,59,60,65,66,67,72,73,78,79,84, 85,91,92,97,98\}$$

$\endgroup$
  • $\begingroup$ I assume that 16 should be added to the list. In fact it consists of the numbers satisfying the equation $$\left\lfloor\frac{3n}{2\pi}\right\rfloor-3\left\lfloor\frac{n}{2\pi}\right\rfloor=1.$$ $\endgroup$ – user May 29 at 8:57
  • $\begingroup$ @user. You are very correct ! I shall edit. Cheers :-) $\endgroup$ – Claude Leibovici May 29 at 9:04

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.